THE USE OF WEBBING TECHNIQUE IN WRITING SPOOF TEXT TO THE CLASS XI IPS AT SMA MUHAMMADIYAH 1 PAMEKASAN - Nurjanuar Ilhami (Universitas Madura, 2018)
Communication devided to be two kinds, oral dan written communication. Writing is the most difficult skill to be mastered. In the fact, writing is one of the important skills that must be learnt by the students. Many students are not interested in writing and regard it as the most difficult skill to learn. To overcome this problem, the teacher should find the appropriate technique to be applied in classroom that makes students be able to produce writing. In this case, the researcher used webbing technique as a tool to overcome the problem. The purpose of this research is to find out an improvement in learning spoof text through webbing technique toward students’ writing skill. The method which was used in this research was qualitative Research. at SMA Muhammadiyah 1 Pamekasan and it involved 20 students at the class XI IPS as the respondents. Based on the results of this research, the implementation of webbing technique in teaching spoof text has shown a good achievement. The data of the implementation of the technique showed 18 students who felt easy and successfully understand how to make webbing technique. The students also felt happy in doing the subject because the technique was simple for students to apply in writing. In the result of cycle 1, there were 18 students from 20 students who passed the KKM by the mean 85.75. On the other hand, the questionnaire results showed the students’ response toward the use of webbing technique were positive. 80% students or 16 students felt interested to the webbing technique. The students looked enthusiastic and seriously in discussion. In short, students’ responses to learn were generally positive. Based on these findings, it could be concluded that the use of webbing technique could improve students’ writing skill of class XI IPS at SMA Muhammadiyah 1 Pamekasan.